Kinetics of Severe Acute Respiratory Syndrome (SARS) Coronavirus-Specific Antibodies in 271 Laboratory-Confirmed Cases of SARS - He, Zhongping (American Society for Microbiology, 2004)
The sensitivities and specificities of an immunofluorescence assay and an enzyme immunoassay for detection of antibodies specific for severe acute respiratory syndrome coronavirus (SARS-CoV) were compared for 148 laboratory-confirmed SARS cases. The appearance and persistence of SARS-CoV-specific antibodies were assessed, with immunoglobulin G detected in 59% of samples collected within 14 days and persisting for 60 to 95 days after the onset of illness.